YOUTH PERCEPTIONS OF VIOLENCE IN MEXICO, AN EXPLORATORY STUDY - Linda D. Russell (European Scientific Journal, ESJ, 2015)
Violence and youth are key issues in contemporary society, whether youths are the victim of violence as in the case of the student teachers in Mexico, or the perpetrators of violence, as in the case of Western adepts to the ISIS jihadist cause. This paper analyses the results of a recent online exploratory survey by the author of youth perceptions of violence in Mexico in comparison with national statistics generalised across the adult age group. The outcome is discussed in relation to the ongoing investigation into the disappearance of the rural student teachers in Guerrero, Mexico and Wilkinson’s and Pickett’s global analysis of the relation between social and economic inequality and the increase in violent crime. Finally these issues are related to Mexican family values and morality in order to gauge the possible challenges involved in addressing the factors involved in the issues raised.